2 ',3 '-cyclic nucleodide 3 '-phosphodiesterase cells derived from transplanted marrow stromal cells and host tissue contribute to perineurial compartment formation in injured rat spinal cord - Cao, Qiong (WILEY, 2020)
10.1002/jnr.21092